2017
DOI: 10.1021/jacs.7b10591
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Lipid Nanodisc Fomation by Amphiphilic Polymethacrylate Copolymers

Abstract: There is a growing interest in the use of lipid bilayer nanodiscs for various biochemical and biomedical applications. Among the different types of nanodiscs, the unique features of synthetic polymer-based nanodiscs have attracted additional interest. A styrene–maleic acid (SMA) copolymer demonstrated to form lipid nanodiscs has been used for structural biology related studies on membrane proteins. However, the application of SMA polymer based lipid nanodiscs is limited because of the strong absorption of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
153
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 106 publications
(162 citation statements)
references
References 41 publications
5
153
0
Order By: Relevance
“…This was further confirmed by the carbonyl carbon resonance (≈185–180 ppm) and the appearance of new peaks in the aliphatic region (CH 2 ≈32 ppm, CH 3 ≈17 ppm, and quaternary C≈54 ppm) in 13 C‐CPMAS NMR spectra of the synthesized polymers as compared to PAA starting material (Figure c). 1 H‐NMR spectra were used to estimate the extent of functionalization by integration (Figure S1, Supporting Information) to be ≈40–50%, within the range of optimal hydrophobic to hydrophilic ratio as seen previously for nanodisks …”
Section: Properties Of Alkyl‐paa‐dmpc‐nanodisksmentioning
confidence: 94%
See 2 more Smart Citations
“…This was further confirmed by the carbonyl carbon resonance (≈185–180 ppm) and the appearance of new peaks in the aliphatic region (CH 2 ≈32 ppm, CH 3 ≈17 ppm, and quaternary C≈54 ppm) in 13 C‐CPMAS NMR spectra of the synthesized polymers as compared to PAA starting material (Figure c). 1 H‐NMR spectra were used to estimate the extent of functionalization by integration (Figure S1, Supporting Information) to be ≈40–50%, within the range of optimal hydrophobic to hydrophilic ratio as seen previously for nanodisks …”
Section: Properties Of Alkyl‐paa‐dmpc‐nanodisksmentioning
confidence: 94%
“…The most common hydrophobic group used in SMA polymer nanodisks is the styrene moiety. It is known that styrene has a strong absorption in the UV region that can interfere with various biophysical techniques, and can also have nonspecific interactions with other aromatic groups from the protein . Recently, two styrene‐free polymers (diisobutylene maleic acid co‐polymer, DIBMA, and polymethacrylate) have been shown to form nanodisks; however there has been no systematic investigation comparing the effects of varying the hydrophobic functional groups used in the formation of nanodisks.…”
Section: Properties Of Alkyl‐paa‐dmpc‐nanodisksmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the recently developed polymers that vary in charge and can form lipid nanodiscs would be valuable to trap the intermediate structures of SEVI in different membrane compositions . In addition, the use of “styrene‐free” methacrylate polymer nanodiscs would enable high‐throughput screening of conditions by ThT fluorescence and CD experiments as demonstrated recently …”
Section: Intrinsically Disordered Pap248–286 Adapts a Partial Helicalmentioning
confidence: 99%
“…Among such peptides, we have successfully demonstrated that 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 22 A and 4F can be used for P450's metabolon reconstitution. [57] 3. 4F was developed by Kariyazono et al [51] and has been shown to overcome some of the technical limitations of 22 A, including high versatility in lipid composition and stability during the size-exclusion chromatography steps necessary for nanodiscs' purification.…”
Section: From Msp To Peptide-based Lipid Nanodiscsmentioning
confidence: 99%